The Foreign Language Syllabus: Design, Evaluation and Renewal - KARA, S (Journal of Human Sciences, 2001)
As any educational activity, teaching a foreign language requires a planning of a set of steps that are made of teaching elements, which are selected and graded according to particular approaches. The arrangement of these elements takes place within the scope of what is known as ‘syllabus’. This article attempts to shed light on the complex task of syllabus design, evaluation and renewal. To this end, contributions of several scholars in this domain would be pinpointed R;mson il`! R-SA'>Constantine